Deep ocean wave energy systems (DOWES): experimental investigations (Journal of Naval Architecture and Marine Engineering, 2014)
Deep water offshore structures have access to very powerful ocean waves by virtue of their location and site condition. Should the energy possessed by these waves be harnessed, it can be one of the popular green energy systems. Present study aims at the design and development of a new device that can be fitted on an offshore semisubmersible platform and can produce electricity to meet their operational energy demands partially. Few wave energy devices are developed in the recent past; Common idea in all such devices is that they harness heave, or surge energy of the wave. In the present study, heave energy of the buoy is converted to mechanical work by deploying hydraulic cylinders and a motor. The generated power from the waves shall be primarily utilized in the semi-submersible platform for deep sea mining application.DOI: http://dx.doi.org/10.3329/jname.v11i2.18420